Detection of hand, foot and mouth disease in the Yucatan Peninsula of Mexico - Carlos Machain-Williams; Alma R. Dzul-Rosado; Aarón B. Yeh-Gorocica; Katia G. Rodriguez-Ruz; Henry Noh-Pech; Lourdes Talavera-Aguilar; Ma. Isabel Salazar; María Eugenia Castro-Mussot; Guadalupe Reyes-Solis; Julián E. Garcia-Rejon; Fernando I. Puerto-Manzano; Bradley J. Blitvich (MDPI AG, 2014)
We report a case of hand, foot and mouth disease (HFMD) in a 5-year-old male from Merida City in the Yucatan Peninsula of Mexico. A clinical and physical examination revealed that the patient had symptoms typical of HFMD, including fever, fatigue, odynophagia, throat edema, hyperemia, lesions on the hands and feet, and blisters in the oral cavity. The patient fully recovered after a convalescence period of almost three weeks. Reverse transcription-polymerase chain reaction and nucleotide sequencing revealed that the etiological agent was enterovirus 71 (EV71). The sequence has greatest (90.4%) nucleotide identity to the corresponding regions of EV71 isolates from the Netherlands and Singapore. Although HFMD is presumably common in Mexico, surprisingly there are no data in the PubMed database to support this. This case report provides the first peer-reviewed evidence of HFMD in Mexico.